EKPLORASI OBJEK BERGERAK DENGAN FOTOGRAFI TIGA WARNA - Waskito, Setyo Bagus (Seni Media Rekam ISI Surakarta, 2015)
Three-color photography is a technique used to produce color photography in the past. Because the shooting is not simultaneous then this technique producesan image that is not perfect at moving objects such as lines of color on the edges of moving objects or shadows are brightly colored when objects move quickly. A weakness in these techniques will be explored and done intentionally shooting at moving objects to get different effects and artistic in a work of art photography.Keywords: photography, exploration, motion, color, and effects.